The Role of the Department of Trade and Industry in the Development of Small and Medium Enterprises (SMEs) in the Food Sector of Tanjung Pinang City - Putra, Erlangga Eka; Nazaki, Nazaki; Sophia, Uly (Formosa Journal of Applied Sciences, 2024)
The role of Small and Medium Enterprises (SMEs) in the food sector holds significant relevance in the economic development of Tanjung Pinang City. The Department of Trade and Industry of Tanjung Pinang City continues to drive economic growth through Small and Medium Enterprises (SMEs). Furthermore, the food sector is the largest industry, with a total of 1,586 enterprises. This research aims to examine the role of the Department of Trade and Industry in the development of Small and Medium Enterprises (SMEs) in the food sector of Tanjung Pinang City by applying Soerjono Soekanto’s theory. This research employs a qualitative method. Based on the findings, it can be concluded that the role of the Department of Trade and Industry of Tanjung Pinang City as a regulator, dynamist, and facilitator for SMEs in the food sector has been implemented but is not yet effective in developing food SMEs.